Wheat Grain Yield and Protein Concentration Response to Nitrogen and Sulfur Rates - Brent R. Jaenisch; Tara Wilson; Nathan O. Nelson; Mary Guttieri; Romulo P. Lollato (Kansas Agricultural Experiment Station Research Reports, 2020)
Winter wheat is often double-cropped after soybeans in no-tillage systems. The soybean crop removes large quantities of sulfur (S), which might cause S deficiency for the following wheat crop. Our objective was to evaluate the responses of three wheat varieties to three nitrogen (N) and four S fertilizer rates representing a range of N:S ratios. The experiment was conducted near Ashland Bottoms and Hutchinson, KS. Treatments were arranged as a complete factorial structure with a split-split-plot design. Variety was the whole-plot, N was the sub-plot, and S was the sub-sub plot. Nitrogen rates were 50, 100, and 150% of the university recommendations for a 60 bushel per acre yield, and S rates were 0, 10, 20, and 40 pounds of S per acre. Wheat varieties evaluated were Zenda, SY Monument, and LCS Mint. Increasing the N rate increased grain yield at both locations. Sulfur increased grain yield at Ashland Bottoms but not at Hutchinson. Nitrogen by S interaction occurred for protein concentration at both locations. At Hutchinson, N rates of 50, 100, and 150% N resulted in grain yield of 62, 73, and 78 bu/a. For the 50% and 100% N rate, protein concentration was 10.8% and 11.3%; however, the 150% N rate with 20 or 40 lb S/a increased protein concentration to 11.8% as compared to 11.5% observed in the 0 or 10 lb S/a treatments. At Ashland Bottoms, N rates of 50, 100, and 150% resulted in grain yield of 56, 69, and 74 bu/a across S treatments. For the 0 pounds of S per acre treatment, though, these N rates resulted in grain yields of 36, 42, and 40 bu/a. The 150% N rate with 20 and 40 lb S/a increased grain yield by 5 bu/a as compared to the 10 lb S/a treatment. At the 50% N rate, protein concentration was 9.7% with an application of S as compared to 10.3% for the 0 lb S/a, which is due to a dilution effect from the increased grain yield. As S application increased, protein concentration decreased at the 100% N rate. However, at the 150% N rate, protein concentrations were 12.2, 11.5, 11.8, and 11.9% for the 0, 10, 20, and 40 lb S/a, respectively. Our results suggest that a balanced fertilization of N and S are essential for improving yield and protein concentration in no-till systems following soybeans, and that initial S in the profile and soil organic matter (OM) play a crucial role in determining the crop’s response to the added fertilizers.
Keywords: sulfur; nitrogen; wheat; Triticum aestivum L.; fertility; ratio; protein